Perception of people with arterial hypertension about aspects that influence treatment adherence - Paulo Roberto de Oliveira Miranda; Débora de Oliveira Sacramento; Flavia Batista Barbosa de Sá Diaz; Luana Vieira Toledo; Renan Sallazar Ferreira Pereira; Katiusse Rezende Alves (Universidade Federal de Santa Maria, 2021)
Objective: to describe the perception of people with arterial hypertension of the aspects that facilitate and hinder treatment adherence. Method: descriptive qualitative study developed with 16 people met in Nursing consultations. Interviews were conducted with a semi-structured guide and the content analysis technique was used. Data were collected between January and August 2017. Results: having willpower, family and multidisciplinary support, knowledge about the pathology and forms of prevention and fear of death facilitated adherence; on the other hand, little knowledge, laziness, lack of urban infrastructure and climatic conditions, habit of consuming unhealthy foods, alcoholic beverages and tobacco, cost of treatment and forgetfulness of taking the medication hindered adherence. Conclusion: the treatment of hypertension causes changes in the dynamics of life, being essential to have willpower, family and professional support, in addition to overcoming unhealthy habits.